RECORDING INFORMATION SYSTEM FOR GOODS OWNED INVENTORY/ ASSET STATE ENVIRONMENT WATER RESOURCES DIRECTORATE OF THE CENTRAL REGION USING UNIFIED MODELING LANGUAGE (UML) AND VISUAL BASIC. NET - MUHAMMAD YUSUF; Melani Dewi Lusita, SKom, MMSI (Jurnal Sistem Informasi, 2006)
The increasing activities of environmental goods inventory records of Water Resources Directorate of the Central Region and the growing need for a wide range of information the writer trying to help create a system of recording information goods. In an inventory recording system is not using the applications allow a user in data processing, result in errors due to miscalculations or different data transfer with the input. By using the recording application of the proposed inventory, incoming data is expected to be in accordance with the expected output, so that common mistakes can be reduced to a minimum.